2022
DOI: 10.3389/fmed.2021.804892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Rheumatologic Pain in Cystic Fibrosis Adult Patients

Abstract: BackgroundWith the improvement of cystic fibrosis (CF) patient survival, the prevalence of long-term complications increased, among them rheumatologic disorders.MethodsThe aim of this prospective study was to evaluate the prevalence of spinal and joint pain, and their impact on disability, anxiety, depression, and quality of life in CF adult patients.ResultsForty-seven patients were analyzed, 72% of men, mean aged 28 years, with a mean body mass index of 22 kg/m2 and a mean FEV1% of 63%. Twenty-two patients (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…This may reflect the findings of recently published studies in CF that GI symptom scores were found to be higher in female participants 4,13 . However, we do acknowledge that sex differences were not seen in all studies, with studies by Mainz et al finding no difference in GI symptoms based on sex 2,12 . The lower number of male participants prevented sub-analysis of the results by modulator status and gender and so conclusions around GI symptoms based on gender cannot be drawn in this survey.…”
Section: Limitationscontrasting
confidence: 51%
See 1 more Smart Citation
“…This may reflect the findings of recently published studies in CF that GI symptom scores were found to be higher in female participants 4,13 . However, we do acknowledge that sex differences were not seen in all studies, with studies by Mainz et al finding no difference in GI symptoms based on sex 2,12 . The lower number of male participants prevented sub-analysis of the results by modulator status and gender and so conclusions around GI symptoms based on gender cannot be drawn in this survey.…”
Section: Limitationscontrasting
confidence: 51%
“…Common gastrointestinal symptoms include abdominal pain, flatulence, bloating, and foul-smelling stools 2,3 , with over one in five pwCF reporting moderate to severe gastrointestinal symptoms 4 . Approximately 85% of pwCF are pancreatic insufficient necessitating the need for pancreatic enzyme replacement therapy (PERT) and between 2-5% each year will develop distal intestinal obstruction syndrome (DIOS) 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…[12] We recently showed a more important impairment on HAQ scale in patients with both spinal and joint pain. [4] CF quality of life is associated with several factors including FEV 1 %, BMI, pulmonary exacerbations, and depression and anxiety. [23,24] Several limitations of our study have to be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatologic pain and arthritis were assessed using a questionnaire as previously described. [ 4 ] For this study, the question regarding spinal pain (“Did you have spinal pain?”) was considered.…”
Section: Methodsmentioning
confidence: 99%
“…22 пациента (47%) описали ревматологическую боль либо в позвоночнике (n = 15,32%), либо в суставах (n = 14,30%). Пациенты с болями в позвоночнике и / или суставах были ниже ростом (р = 0,023), чаще колонизированы Staphylococcus aureus (р <0,008), чаще имели гомозиготные мутации ΔF508 (р = 0,014) [70]. В педиатрической практике группа ученых под руководством V. Comanici изучала распространенность артрита, связанного с МВ.…”
Section: муковисцидоз и ревматологические заболеванияunclassified